Innovative Strategies for Strengthening the Competitiveness of Wan Alan MSME through Production Technology Advancement and Digital Marketing - Adisti, Adila; Devi Yulia Rahmi; Wellyalina (Warta Pengabdian Andalas, 2025)
This community service program aims to strengthen the production and digital marketing capacity of the Wan Alan Micro, Small, and Medium Enterprises (MSME), a home–scale spice producer in Padang Panjang, West Sumatra. The intervention was motivated by the partner’s limited production technology, absence of standardized SOPs, lack of product testing, weak brand protection, and suboptimal digital marketing performance. The activities were carried out through training, technology adoption, mentoring, proximate testing, Standard Operating Procedure (SOP) development, brand IPR registration assistance, photography, videography workshops, and digital marketing coaching. The results show significant improvements: production capacity increased, sterilization time decreased, SOPs and cost of goods sold (COGS) calculations were implemented, proximate tests were completed, and trademark registration progressed to the substantive examination stage. In the marketing aspect, visual content quality improved substantially, Instagram performance increased by more than 233%, and new distribution channels were opened through a formal partnership with Budiman Supermarket. These outcomes demonstrate that integrated assistance combining production technology, operational standardization, and digital marketing enables MSMEs to enhance competitiveness, expand market reach, and strengthen business sustainability.